Encyclopedia of Polymer Science and Technology 2014
DOI: 10.1002/0471440264.pst618
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Glycopolymers

Abstract: Multimeric representations of carbohydrates play a pivotal role in many biological processes. Polymer chemists aim at copying these biologically active biopolymers by the design of glycopolymers, synthetic polymers with pendant sugars. This article is focused on the synthetic methods as well as applications of these macromolecules. Since the first description of glycopolymers in the late 1950s, a myriad of glycopolymer structures have been reported. The first glycopolymer was prepared via free radical polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 209 publications
0
6
0
Order By: Relevance
“…Glycopolymers can be prepared either by post-polymerization modification, which consists in the functionalization of a preformed polymeric backbone, or in the polymerization of glycosylated monomers [ 51 , 52 ] that can be performed by several synthetic routes that provide controllable architectures, stereochemistry, and molecular weights, such as free radical polymerization (ring-opening polymerization (ROP)), ionic polymerization, controlled radical polymerization (nitroxide-mediated polymerization (NMP), atom transfer radical polymerization (ATRP), reversible addition fragmentation chain transfer (RAFT), and enzyme-mediated polymerization [ 51 , 53 , 54 , 55 ]. Here, we will focus on the post-functionalization of polymeric nanoparticles with carbohydrates, as it allows the attachment of pendant carbohydrate moieties ( Figure 3 ), making it ideal for targeted delivery.…”
Section: Carbohydrate-functionalized Polymeric Nanoparticlesmentioning
confidence: 99%
“…Glycopolymers can be prepared either by post-polymerization modification, which consists in the functionalization of a preformed polymeric backbone, or in the polymerization of glycosylated monomers [ 51 , 52 ] that can be performed by several synthetic routes that provide controllable architectures, stereochemistry, and molecular weights, such as free radical polymerization (ring-opening polymerization (ROP)), ionic polymerization, controlled radical polymerization (nitroxide-mediated polymerization (NMP), atom transfer radical polymerization (ATRP), reversible addition fragmentation chain transfer (RAFT), and enzyme-mediated polymerization [ 51 , 53 , 54 , 55 ]. Here, we will focus on the post-functionalization of polymeric nanoparticles with carbohydrates, as it allows the attachment of pendant carbohydrate moieties ( Figure 3 ), making it ideal for targeted delivery.…”
Section: Carbohydrate-functionalized Polymeric Nanoparticlesmentioning
confidence: 99%
“…In the polymer field, these renewable raw materials have been widely used in recent years and many studies have been performed to produce a wide range of monomers and polymers based on carbohydrates . Polymers with carbohydrates moieties, named glycopolymers, have been prepared using two main routes: synthesis of carbohydrate‐based monomers, followed by their polymerization, and functionalization of polymers with carbohydrates . Glycopolymers based on carbohydrate methacrylate were first reported by Haworth and co‐workers, who prepared crosslinked and hard polymers from sorbitol and mannitol (meth)acrylates …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Polymers with carbohydrates moieties, named glycopolymers, have been prepared using two main routes: synthesis of carbohydrate-based monomers, followed by their polymerization, and functionalization of polymers with carbohydrates. [4][5][6][7] Glycopolymers based on carbohydrate methacrylate were first reported by Haworth and co-workers, who prepared crosslinked and hard polymers from sorbitol and mannitol (meth)acrylates. 8 Carbohydrate (meth)acrylate-based polymers combine an apolar backbone with polar carbohydrate moieties, which endow polymers with water solubility without backbone degradation.…”
Section: Introductionmentioning
confidence: 99%
“…FRP is the most common type of polymerization in the industry, accounting for around 40–45% of all industrial polymers due to its simplicity and tolerance to impurities which reduces costs. Several studies have demonstrated that glycopolymers synthesized via FRP possess adequate affinity to biological targets, although they are polydisperse. , A brief summary of potential applications of glycopolymers synthesized with FRP has been reported by Babiuch and Stenzel . We expect that in the future, the use of FRP will increase the viability of these applications at large scale.…”
Section: Introductionmentioning
confidence: 94%
“… 1 , 23 A brief summary of potential applications of glycopolymers synthesized with FRP has been reported by Babiuch and Stenzel. 24 We expect that in the future, the use of FRP will increase the viability of these applications at large scale. We anticipate that the introduction of a biobased molecule with mannose moieties would lead to a certain degree of affinity for lectins, viruses, and/or toxins, and that such interactions can be tuned for specific applications.…”
Section: Introductionmentioning
confidence: 99%